Investigating the evolutionary impact of the teleost genome duplication through comparative genomics and phylogenetic analysis of homeobox genes in the Osteoglossomorpha - Martin, K (2016)
Multiple rounds of whole genome duplication (WGD) have played a pivotal role in the expansion, elaboration, and evolutionary diversification of vertebrate genomes. In addition to sharing two rounds of whole genome duplication with all other vertebrates, a teleost-specific genome duplication (TGD) occurred in the stem of the teleost lineage ∼350 million years ago (MYA) and is thus a genomic synapomorphy shared by all ∼26,000 extant species. The TGD has variously been implicated in accelerated speciation, evolution of morphological complexity, increased rates of molecular evolution, and the evolution of novelty, and therefore is therefore of significant interest for its impact on teleost evolution and also as a model for understanding the evolutionary patterns and processes which accompany WGDs more generally. Investigation of the TGD has contributed extensively to the general understanding of WGDs however, until the present work, a relatively narrow taxonomic sampling of species within a single teleost subdivision, Clupeocephala, have been investigated. This taxonomic bias has left potentially relevant evolutionary changes to the teleost genome in the immediate wake of the TGD obscured. Due to their deeply branching ancestry, species belonging to the two other major teleost subdivisions, Osteoglossomorpha and Elopomorpha, are well positioned for deeper comparative genomic analyses of the TGD and the accompanying phenomenon of diploidization. The focus of the present work has been to develop the first genomic resources specifically for osteoglossomorphs and to investigate the evolutionary patterns and processes which accompanied diploidization prior the deep divergence of the three extant teleost subdivisions. To this end, I have generated de novo genome and transcriptome data from four osteoglossomorph taxa (Pantodon buchholzi, Osteoglossum bicirrhosum, Chitala ornata, and Gnathonemus petersii) and conducted comparative genomic and phylogenetic analysis with other teleosts and pre-TGD vertebrates including the gar Lepisosteus oculeatus. With a focus on Hox and other ANTP class homeobox-containing transcription factor families I provide evidence that speciation of the major teleost subdivisions occurred prior to the termination of the diploidization process following TGD and discuss the evolutionary implications of this model. Beginning with an analysis of the Hox clusters in P. buchholzi I show that divergent resolution of TGD-generated Hox duplicates occurred both at the individual gene level as well as at the level of whole cluster losses. Detailed phylogenetic analyses of the P. buchholzi Hox clusters further revealed that the transition from polyploid alleles to full paralogs during the diploidization process can occur independently in different lineages when speciation rapidly follows WGDs, causing duplicated genes to exhibit a special case of four-way gene homology which I have termed ‘tetralogy’. A genome-wide survey of ANTP class homeobox genes in a de novo assembly of the P. buchholzi genome revealed that ancient TGD duplicates of at least 14 subfamilies were preserved uniquely in the P. buchholzi genome and lost from clupeocephalan teleosts. Finally, by comparing the Hox complements in gar and P. buchholzi with three additional osteoglossomorphs I show that the diversity in potential duplicate resolution patterns is also highly variable between osteoglossomorph families. Overall, this work highlights the importance of considering not only the relative timing of gene duplication and speciation in comparative genomic analyses but also their timing relative to diploidization. Going forward, the research community will need to carefully evaluate the effects differences in diploidization rate and pattern, both between lineages and across the genome, have had in influencing the fate of individual gene duplicates as well as upon the macroevolutionary phenomena frequently correlated with WGDs more generally.